2021
DOI: 10.12957/reuerj.2021.57581
|View full text |Cite
|
Sign up to set email alerts
|

Condições de saúde de mulheres e homens idosos com idade avançada: estudo longitudinal

Abstract: Objetivos: descrever as características sociodemográficas e de saúde de mulheres e homens com 75 anos ou mais de idade, no baseline e follow-up de quatro anos e verificar para mulheres e homens as mudanças nas condições de saúde. Métodos: estudo longitudinal com 109 idosos de 75 anos ou mais de idade de um município no Triângulo Mineiro. A coleta dos dados, realizada em dois momentos (2014-2018), ocorreu no domicílio com a aplicação de instrumentos validados no Brasil. Procederam-se às análises descritiva e te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(76 reference statements)
0
1
0
3
Order By: Relevance
“…A study in San Antônio, Texas, pointed out that pre-frail individuals were more likely to regress their stage in relation to frail ones, but showed that the higher the frailty stage, the higher the mortality 18 . In another longitudinal study, in Triângulo Mineiro, it also showed worsening in the health conditions of the older people, with women being more frail than men 19 . These results suggest that there is an important variation between frailty levels over time, which reinforces the dynamic nature of the frailty process 12,20 .…”
Section: Discussionmentioning
confidence: 91%
“…A study in San Antônio, Texas, pointed out that pre-frail individuals were more likely to regress their stage in relation to frail ones, but showed that the higher the frailty stage, the higher the mortality 18 . In another longitudinal study, in Triângulo Mineiro, it also showed worsening in the health conditions of the older people, with women being more frail than men 19 . These results suggest that there is an important variation between frailty levels over time, which reinforces the dynamic nature of the frailty process 12,20 .…”
Section: Discussionmentioning
confidence: 91%
“…Tais dados podem relacionar-se a maior expectativa de vida feminina e, consequentemente, a maiores taxas de doenças crônicas que predispõem a diminuição da capacidade funcional. (20) O estudo INTERSTROKE mostrou que 90% dos AVC estavam associados a dez fatores de risco como HAS, DM, dislipidemia, dieta inadequada, sedentarismo, razão cintura/quadril aumentada, tabagismo, etilismo, depressão e cardiopatias (FA e doença coronariana). (21) Dentre esses, quatro foram observados no presente estudo incluindo a HAS, a mais prevalente, DM, dislipidemia e FA.…”
Section: Discussionunclassified
“…Tais dados podem relacionar-se a maior expectativa de vida feminina e, consequentemente, a maiores taxas de doenças crônicas que predispõem a diminuição da capacidade funcional. (20) O estudo INTERSTROKE mostrou que 90% dos AVC estavam associados a dez fatores de risco como HAS, DM, dislipidemia, dieta inadequada, sedentarismo, razão cintura/quadril aumentada, tabagismo, etilismo, depressão e cardiopatias (FA e doença coronariana). (21) Dentre esses, quatro foram observados no presente estudo incluindo a HAS, a mais prevalente, DM, dislipidemia e FA.…”
Section: Discussionunclassified